Evaluation of the marginal adaptation and debonding strength of two types of CAD-CAM implant-supported cement-retained crowns - Nada Ahmed Ramzy; Amir Shoukry Azer; Mohamed Moataz Khamis (BMC, 2023)
Abstract Background In-vitro data from a clinically well-known lithium disilicate ceramic reference was used to assess the expected performance of resin-based materials in implant dentistry. The purpose of the study was to compare the bond strength and marginal adaptation of nano-ceramic hybrid composite crowns cemented to stock cement-retained abutments to lithium disilicate crowns. Methods Twenty abutment analogs were embedded into auto-polymerizing acrylic resin blocks. The blocks were divided into 2 groups according to the restorative crown material. The 2 groups were divided as follows: Resin nano-ceramic group and lithium disilicate group. Abutment analogs in both groups were scanned using a laboratory scanner, and the restorations were designed, manufactured, and cemented with resin cement over the corresponding group. All samples were tested for marginal adaptation and bond strength after storage for 24 hours at 37 °C in 100% humidity. Data were collected, tabulated, and statistically analysed using the appropriate tests. Normality was checked using Shapiro Wilk test and Q-Q plots. Data were normally distributed. Variables were presented using mean, 95% Confidence Interval (CI) and standard deviation in addition to median and Inter Quartile Range (IQR). Differences between groups regarding debonding forces was assessed using independent t test. Two Way ANOVA was performed to assess the effect of material and bonding on marginal gap. All tests were two tailed and p value was set at < 0.05. Results Marginal gap and debonding force values were significantly different according to the type of material used (P < .05). Resin nano-ceramic crowns presented lower marginal gap values before (20.80 ± 8.87 μm) and after (52.11 ± 22.92 μm) bonding than lithium disilicate crowns. The debonding force value for resin nano-ceramic crowns (284.30 ± 26.44 N) was significantly higher than that for lithium disilicate crowns (253.30 ± 33.26 N). Adhesive failure mode was detected in all the specimens in both groups. Conclusions The type of material used for implant-supported cement-retained crowns had a statistically significant effect on marginal adaptation and bond strength. Resin nano-ceramic implant-supported cement-retained crowns had better marginal adaptation and higher bond strength than those manufactured using lithium disilicate.